Association Between the Consumption of Breakfast and the Recommendation of Physical Activity and the Nutritional Status in Children [Associação Entre O Consumo de Café Da Manhã Com a Recomendação de Atividade Física E O Estado Nutricional Em Crianças] - De Moraes-Ferrari, G (Associacao Brasileira de Pos - Graduacao em Saude Coletiva, 2021)
The scope of this article is to associate breakfast consumption (BC) with moderate to vi-gorous physical activity (MVPA) intensity and the nutritional status of children aged 9-11. The sample consisted of 432 children from São Caetano do Sul participating in the International Study of Childhood Obesity Lifestyle and the Environment. Data were collected between 2012 and 2013. The weekly BC was obtained using the self-reported method. To measure MVPA, children used ac-celerometers and were classified into two groups (<60 versus ≥60 min/day). The nutritional status was presented by body mass index (BMI). Logistic regression models were used, adjusted for gender, age, race, parental educational level and eating score. The mean BC was 5.25 (CI95%: 5.1-5.4) days/week and the MVPA was 59.29 (CI95%: 57.3-61.7) min/day. In the total sample, 55.8% of the children did not perform ≥60 min/day of MVPA and 50.2% were overweight or obese. The daily BC was not associated with MVPA, however, it reduced the odds of children being overweight or obese (OR: 0.51; CI95%: 0.34-0.76; p=0.001). Daily BC reduced the odds of excess weight or obesity in children, though it did not increase the chances of children meeting the recommendations of MVPA. Public policies should encourage daily BC to prevent excess weight or obesity. © 2021, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All rights reserved.
Keywords: Obesity; Eating behavior; Child